Advancing multidisciplinary management of pediatric hyperinflammatory disorders - Francesco La Torre; Giovanni Meliota; Adele Civino; Angelo Campanozzi; Valerio Cecinati; Enrico Rosati; Emanuela Sacco; Nicola Santoro; Ugo Vairo; Fabio Cardinale (Frontiers in Pediatrics)
Pediatric hyperinflammatory diseases, including Still's disease, Kawasaki disease (KD), multisystem inflammatory syndrome in children (MIS-C), and recurrent pericarditis (RP), represent a spectrum of conditions characterized by immune dysregulation and systemic inflammation. Each disorder exhibits distinct pathophysiological mechanisms and clinical features, yet their overlapping presentations often pose diagnostic challenges. Early and accurate differentiation is critical to mitigate complications such as macrophage activation syndrome (MAS), coronary artery aneurysms, and myocardial dysfunction. This narrative review explores the pathophysiology, diagnostic criteria, and management of these conditions, emphasizing the utility of advanced biomarkers, imaging modalities, and genetic testing. For Still's disease, the review highlights the transformative role of biologic therapies targeting IL-1 and IL-6 in reducing systemic inflammation and improving outcomes. In KD, timely administration of intravenous immunoglobulin (IVIG) and combination with high-dose steroids in high-risk patients is pivotal for preventing coronary complications. MIS-C, associated with SARS-CoV-2 infection, requires tailored immunomodulatory approaches, including corticosteroids and biologics, to address severe hyperinflammation and multiorgan involvement. RP management prioritizes NSAIDs, colchicine, and IL-1 inhibitors to reduce recurrence and corticosteroid dependence. The review advocates for a multidisciplinary approach, integrating standardized diagnostic algorithms and disease-specific expertise to optimize patient care. Future research directions include the identification of predictive biomarkers, exploration of novel therapeutic targets, and development of evidence-based treatment protocols to enhance long-term outcomes in pediatric inflammatory diseases.